Koordinasi Dinas Perhubungan dan Satuan Lalu Lintas dalam Penanggulangan Kemacetan Kota Makassar - Rijal Rijal (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2019)
Traffic congestion is caused by an imbalance between the number of vehicles and the number of existing roads. Based on Makassar City Samsat data, the number of vehicles in 2016 reached 1,128,809 units. From 2017 to October 2018 the vehicle reaches 1,563,608 units. The aim of the study was to find out work arrangements, synchronization of activities, manifestation of mutual interests, and shared goals carried out by the Department of Transportation and Traffic Units in managing congestion in Makassar City. This study uses a qualitative descriptive method with a type of case study research. Data collection techniques are obtained through observations, interviews, literature studies and documentation. The results of the study found that the process of coordination of the Office of Transportation and Satua Traffic included; the arrangements used have implemented Area Traffic Control System (ATCS) technology, synchronization has been effective, this joint interest has been running with meetings or meetings conducted between two parties even though the implementation is still not maximal, because meetings are held only 1 to 2 times meeting. Likewise, the cooperation of the Makassar City Satlantas and Dishub is still not maximal in carrying out its duties in overcoming congestion.